PSYCHOLOGY AND INJURED ATHLETE - Rakesh Sangwan (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2024)
Some athletes are prone to concussions, while others are not usually involved for clinical reasons. Regularly, it seems obvious, it is possible that the most notable athletes are the most injured, but perhaps the reverse is attested. Sports fans inevitably regard truly injured players, who return to play in record time, with discomfort to give the system a little psyche to clear. Taking everything into account, some athletes have been known to require psychiatric treatment during rehabilitation.Certainly, even injuries are not required to be seen in the life of athletes, they are basically a part of the legitimacy of every athlete profession. Injury is generally viewed as a primary issue that begins at the time the injury occurred and ends when the athlete is back in business, playing and engaging. Incidentally, injury can affect an athlete's general plans in general when the athlete cannot collapse one's overall specific reach or upset. In addition to injury, credits can be affected through an athlete's assessment, leads, social interactions, and even general appearance. As demonstrated by these certified components, sports injury should be viewed as a more abstract whole than the original issue itself, and should be treated in the same way as a more fundamental aggregate. Psychological reactions to an injury and all recovery can impact the time used and progress of rehabilitation, and return to wear and tear. So clearly psychological responses to an injury need to be taken into account and shape the treatment plan.